Import and Export of Polish Coal in the Interwar Period - Łazor, Jerzy (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The article analyses the evolution of geographical and price evolution of Polish exports of coal, and explains the much smaller imports. Using detailed statistical data, it shows how state intervention (via support for and control of cartelisation of the sector) influenced prices achieved by Polish exporters. More generally, it places the Polish coal policy within the wider set of balance-of-payment supporting measures.